Konsep diri dalam islam dan implikasinya terhadap komunikasi interpersonal sehari-hari - Mushthafa, Abdillah; Nurhidayah, Yayah (PSYCOMEDIA : Jurnal Psikologi, 2024)
Understanding the self concept in the Islamic perspective influences the quality of interpersonal communication. Our research aims to relate a comprehensive understanding of self-concept in Islam to individuals' everyday communication practices. This research employs a qualitative approach with a literature review. The findings indicate that a strong understanding of self-concept in Islam positively impacts interpersonal communication quality. This underscores the importance of integrating religious values into everyday communication practices. In conclusion, understanding the concept of self in Islam can enhance interpersonal relationship quality, providing a significant contribution to the development of psychology as a discipline. Therefore, it is crucial to integrate religious values into communication training programs to strengthen interpersonal skills within society.